PENGARUH LITERASI FINANSIAL DAN KONTROL DIRI PADA PERILAKU FINANSIAL SANTRI BAHAUDDIN (JEA17: Jurnal Ekonomi Akuntansi, 2022)
The purpose of this study was to analyze the effects of financial literacy and self-control on the financial behavior of Santri Bahauddin. This research was conducted at two Islamic boarding schools in Ngelom Sidoarjo, East Java, where these two Islamic boarding schools were chosen because the scientific genealogy of the stakeholders of the two Islamic boarding schools was the same. In collecting data, the research used a self-administered questionnaire. There were 75 students from two Islamic boarding schools who were selected as the sample. This study shows that the financial literacy variable has a positive and significant influence on the financial behavior variable as evidenced by Path Values of 0.0005. And the self-control variable has a positive and insignificant effect as evidenced by Path Values of 0.138